Exploring the Antecedents of Artificial Intelligence Products’ Usage. The Case of Business Students - Rodney Duffett; Rodica Milena Zaharia; Tudor Edu; Raluca Constantinescu; Costel Negricea (Amfiteatru Economic)
This study aims to investigate to what extent facilitating conditions (those means that users consider necessary to use for a certain technology) and other predictors (perceived risk and lack of trust in technology, gender, education, income, technology proficiency and equipment used to access the Internet) influence the use of Artificial Intelligence Products (AIP) in general and for education. Using the Unified Theory of Acceptance and Use of Technology (UTAUT), the data collected, through an online questionnaire from a sample of 450 Romanian business students, were examined using principal component analysis (PCA) and logistic regression. Facilitating conditions indicated a direct effect (positive) on the dependent variables, and the combination between perceived risk and perceived lack of trust in technology displayed an opposite effect (negative) on the dependent variables. Female students showed a greater tendency to use AIPs in general and for education. Undergraduate students were more inclined to use AIPs in general. Students not using smartwatches or personal computers are inclined to use AIPs more in general and for education. This study advances the theory by exploring the actual use of AIPs for educational purposes, developing the UTAUT model by isolating facilitating conditions and using descriptive variables as predictors. At the same time, the present research contributes to enriching the empirical evidence related to UTAUT on the acceptance and use of technology in Romania. The results of the research allow for the formulation of practical recommendations for universities as current and potential providers of AIPs in order to make the educational process more efficient.